Perception of glycerol carbonate as green chemical: synthesis and applications - Gade, Swapna M.; Saptal, Vitthal B.; Bhanage, Bhalchandra M. (Catalysis Communications, 2022)
Glycerol carbonate (GC) is a prominent component in industrial practice and has a remarkable potential for the sophisticated applications. While GC has come into prominence due to the perceived overflow of glycerol (GLY) as a coproduct of biodiesel industry, its contemporary and future downstream applications are driving tremendous interest in recent years. This review comprises strategies for glycerol carbonate synthesis, properties and its applications. The conversion of GLY to GC via transesterification has appeared in consensus to be the most promising route. A detailed explanation of the effect of the catalysts and operating conditions on the GC yield to provide an updated understanding of the process are summarized. Future directions for GC production through catalytic transesterification are also discussed.
Keywords: Biodiesel; biofuels; catalysis; Glycerol; Glycerol carbonate; green chemistry; transesterification